QOLP-24. COMBATING EMOTIONAL DISTRESS AND SOCIAL ISOLATION IN PEDIATRIC BRAIN TUMOR FAMILIES: A CASE STUDY OF A NATIONAL NONPROFIT'S IMPLEMENTATION OF A PEER INTERVENTION TO IMPROVE QUALITY OF LIFE. (12th November 2021) - Riley, Kathy
Abstract: Interpersonal and emotional support issues present some of the deepest and most pervasive challenges for patients and families. In the Pediatric Brain Tumor Foundation's 2018 Community Health Needs Assessment report (n=900), family survey respondents cited patient anxiety and depression as the greatest challenge patients face in nearly one in three cases, with isolation lagging not far behind. Beyond patients, interpersonal and emotional issues represent the dominant category of challenges for families as well. Many parents stated they felt guilty thinking about their problems, as the patient's suffering far exceeded their own, and nearly half reported often neglecting their own well-being at considerable personal cost. To combat these interpersonal and emotional support issues, the Pediatric Brain Tumor Foundation launched a national intervention in 2020 titled the Peer to Peer Mentoring Program. The program matches patients or family members with trained mentor volunteers who have experience facing the challenges that come with a pediatric brain tumor diagnosis. The theoretical framework used to design the intervention is the Social Support theory. This theory is based on the work of House (1981) who defines social support as the functional content of relationships and categorizes four broad types of supportive behaviors: emotional support, instrumental support, informational support and appraisal support (Glanz, Rimer & Viswanath, 2008). The case study explores the technology platform employed to track matches; how matches are made; how mentors are recruited and trained; how mentees are recruited; and how mental health support is provided to mentors. Analysis of peer meeting logs elucidates key themes that emerge in peer encounters as well as key program challenges and how they are being overcome. This theoretical and practical presentation will define the interpersonal and emotional support issues families face, describe the peer intervention's goals and objectives, and report on insights gained and outcomes achieved.